Breeding value of sires based on offspring weaning weight as a recommendation for selecting Kebumen Ongole Grade cattle - Sumadi, S.; Fathoni, A.; Maharani, D.; Ngadiyono, N.; Widayati, D. T.; Noviandi, C. T.; Khusnudin, M. (Diponegoro University, 2017)
The objective of study was to estimate breeding value of sires of Kebumen Ongole grade cattle based on offsprings weaning weight. This research was carried out from August to December 2015 in Urut Sewu area, Kebumen. The calculation of genetic parameter estimation was heritability of weaning weight. The value of heritability was used to calculate the breeding value of sires based on offsprings weaning weight. Heritability was calculated using paternal half-sib correlation with the direct pattern variance analysis. Breeding Value (BV) of sire was calculated by absolute estimated breeding value. The materials used in this study included were data record during the last three years (2013-2015) consisted of 41 sires, 51 dams and 244 calves. Weaning weight data had been corrected based on age of dams, sex and weaning age of 120 days. The results showed that the heritability value of weaning weight was included in high category (0.36 ± 0.21). The highest BV was KJ.J608 (49.76) with a ratio of 231.45%. The results of this study were expected to be the basis recommendation for selecting sires in Kebumen.